Results of TachoSil® associated with fibrin glue as dural sealant in a series of patients with spinal intradural tumors surgery. Technical note with a review of the literature. (March 2019) - Montano, Nicola; Pignotti, Fabrizio; Auricchio, Anna Maria; Fernandez, Eduardo; Olivi, Alessando; Papacci, Fabio
Highlights: CSF leak is a major problem in intradural spinal tumors surgery. Largest IST series with TachoSil® associated to fibrin glue used as dural sealant. Literature review reporting the results of TachoSil® in spine surgery. Using the TachoSil® after dural closure is safe and effective in IST surgery. Better studies needed to evaluate the TachoSil® in degenerative spine surgery. Abstract: A major problem of surgery for intradural spinal tumors (IST) is the occurrence in the post-operative period of a cerebrospinal fluid (CSF) leak. To the best of our knowledge, here we report on the largest series of IST patients in whom the TachoSil® associated to fibrin glue was used as dural sealant in this kind of surgery. Moreover, we extensively reviewed the literature reporting the results of TachoSil® in spine surgery. The data of 35 consecutive surgically treated IST patients were reviewed. In all cases TachoSil® associated with fibrin glue was used as dural sealant. Mean age was 58.14 ± 15.56 years and mean follow-up (FU) was 23.20 ± 9.76 months. The Modified McCormick Scale (MMS) was used to assess the functional status of patients pre-operatively and at latest FU. All article dealing with the use of TachoSil® in spine surgery were included in the literature review. A CSF collection (treated conservatively with needle aspiration and bed rest with no consequence) was observed only in 1 out of 35 cases. No wound infection nor adverse reaction to the TachoSil® occurred during the FU. At latest FU we observed an improvement of MMS grade in 23 patients (65.71%) and a stable functional status in 12 cases (34.28%). According to our experience and the literature review using the TachoSil® after dural closure is safe and effective in IST surgery. Better standardized studies are needed to establish the usefulness of TachoSil® for incidental dural tear in degenerative spine surgery.